In vivo differentiation of induced pluripotent stem cells into neural stem cells by chimera formation. - Hyun Woo Choi; Yean Ju Hong; Jong Soo Kim; Hyuk Song; Ssang Gu Cho; Hojae Bae; Changsung Kim; Sung June Byun; Jeong Tae Do (PLoS ONE)
Like embryonic stem cells, induced pluripotent stem cells (iPSCs) can differentiate into all three germ layers in an in vitro system. Here, we developed a new technology for obtaining neural stem cells (NSCs) from iPSCs through chimera formation, in an in vivo environment. iPSCs contributed to the neural lineage in the chimera, which could be efficiently purified and directly cultured as NSCs in vitro. The iPSC-derived, in vivo-differentiated NSCs expressed NSC markers, and their gene-expression pattern more closely resembled that of fetal brain-derived NSCs than in vitro-differentiated NSCs. This system could be applied for differentiating pluripotent stem cells into specialized cell types whose differentiation protocols are not well established.